The Analysis of the Credit Risk and X-Efficiency for Commercial Banks in the Chinese Banking Industry - Xiang, Mingyu (2013)
Along with China’s fast economic growth, the development of its financial sector has also attracted with attention. After a series of reforms, the banking system remains dominated the financial sector and impacts significantly on the country’s overall growth. In this paper, using an unbalance panel of 39 banks during the period of 2005 to 2012, we are trying to test the change of efficiency levels of the Chinese commercial banks. The parametric approach, Stochastic Frontier Analysis (SFA) is employed for the empirical test. In general, we concluded that in average, the efficiency level of the Chinese commercial banks has deteriorated over the sample period and this might because of the unfavourable economic environment in China, the unstable financial system triggered by the financial crisis and the worsening of the European debt crisis over the past few years. Among the various banking type, the state-owned banks were found of achieving constant improvement in their efficiency and this might because of their bigger size and monopoly power over the market. In addition, among the six variables which try to capture the factors which may impact on the banks’ efficiency level, four of them were found of statistically significant. They are the return to asset ratio, the equity to asset ratio, the loan to deposit ratio and the listing status. For banks that are more willing to accept risks, it may impact negatively on their efficiency level. Key words: Stochastic Frontier Analysis (SFA), State-owned banks, Joint-equity commercial banks, Chinese banking sector